Target signatures for thin surfaces. (4th January 2022) - Cakoni, Fioralba; Monk, Peter; Zhang, Yangwen
Abstract: We investigate an inverse scattering problem for a thin inhomogeneous scatterer in R m, m = 2, 3, which we model as an m − 1 dimensional open surface. The scatterer is referred to as a screen. The goal is to design target signatures that are computable from scattering data in order to detect changes in the material properties of the screen. This target signature is characterized by a mixed Steklov eigenvalue problem for a domain whose boundary contains the screen. We show that the corresponding eigenvalues can be determined from appropriately modified scattering data by using the generalized linear sampling method. A weaker justification is provided for the classical linear sampling method. Numerical experiments are presented to support our theoretical results.